CLASSROOM STRATEGIES TO INTRODUCE STUDENTS TO INTERPERSONAL AND INTERCULTURAL COMMUNICATION IN A GLOBALIZED WORLD - Ms.Sindhu Thomas B, Ms. S. Deepalakshmi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Globalization is a buzzword since 1990s and it had made the world a global village. It has enriched the worldscientifically, culturally and economically. Many developing countries started opening up their economy and have fetched the benefits of it. Other than opening up the economy and liberalising it, countries and societies had to change their traditional ideas of communication. Interpersonal communication gained more importance since business communications were no more inland.This started the inclusion of interpersonal communication skills in higher education and mushrooming of institutes that nurture such soft skills. Communication between the various cultures became inevitable in the global village. Slowly intercultural studies intensified. Typecasting people had reduced compared to the previous century as a result of cultural exposures.Understanding various cultures slowly. led to increased interpersonal communication. In a country like ours which is an outsourcing hub, interpersonal skills and understanding various cultures and more importantly knowing one’s own culture has become important. These exposures can be given right away from our classrooms. Every classroom is a concoction of various cultures. Various strategies can be used in the classroom to make every student to understand the culture of fellow students and cultures from around the world. These exposures could result in several benefits like better understanding of the world, cultural tolerance, brotherhood, decrease in conflicts, etc. This paper sheds light on the most needed soft skills of the century – interpersonal and intercultural communication skills.